Mechanical Analysis Of Limestone In Jaya, Lhong, And Lhoknga - Raihan .; Fadhli Syamsudin; Lono Satrio (PSI-Aceh, 2012)
Research about mechanical analysis of limestone in District Jaya, Lhong, and Lhoknga has been done from Dec. 2011 to Mei 2012. This study aim is to classify the limestones based on physical and mechanical tests as well as identify opportunities limestone utilization in accordance with the SII 0378-80 as a condition of quality natural stone for building. Research have been done by testing compressive strength, modulus Young, wear, specific gravity, porosity, and absorption. The result shows that the limestones are qualified natural stone for building the foundation, curbstone, stone and ornamental stone or paste.